Artigo 489, § 1º, inciso IV, do Código de Processo Civil de 2015 : o enfrentamento dos argumentos das partes - Padilha, Letícia Marques (2018)
The duty to state reasons for judicial decisions is provided in art. 93, subsection IX, of the Constitution of the Federative Republic of Brazil of 1988. In infraconstitutional legislation it was already present in the procedural documents of 1939 and 1973. However, the Code of Civil Procedure of 2015 sought to improve what is already provided for in constitutional and infraconstitutional legislation. The present study draws an analysis of art. 489, paragraph 1, of the Code of Civil Procedure of 2015, explaining what cannot be considered a reasoned decision. More specifically, subsection IV of the article, which provides for the obligation of the judge to face all the arguments brought by the party who, at least in theory, can contradict the conclusion adopted in the decision and, therefore, to base a position different from that of the judgmental. As the excessive volume of litigation that has weakened respect for the duty to state reasons has become more frequent among us, through decisions based on ready-made utterances of empty character. The idea of said device is to reinforce that the magistrate cannot choose the arguments of the succumbing party that wants to face. It ceases to be relevant in the process only what the magistrate arbitrarily believes to be worthy of consideration, and everything that could lead to a result different from that obtained has become important. The purpose of art. 489, paragraph 1, subsection IV, of the Code of Civil Procedure of 2015 is that if the decision does not analyze all the fundaments of the succumbing thesis, whether invoked by the author or defendant will be considered invalid for lack of reasoning. And the lack of reasoning goes against the constitutionally foreseen, thus facing the Democratic State of Law.